Comparison of standard 4-row versus 6-row3-D linear cutter stapler in creation of gastrointestinal system anastomoses: a prospective randomized trial (Clinics, 2012)
OBJECTIVE: This prospective study was conducted to compare the clinical outcomes of a 6-row 3-D linear cutter with the standard 4-row linear cutter in patients who underwent elective gastrointestinal surgery anastomosis. METHOD: Patients who underwent elective open gastrointestinal surgery that included stapled anastomosis using a linear cutter (Proximate®, Ethicon Endo-Surgery, Cincinnati, OH) between January 2011 and May 2011 were included in the study. The patients were randomly assigned to two groups according to the linear cutter that was used in the surgery: the standard 4-row cutter (the S group) or the new 6-row cutter (the N group). The groups were compared based on the patient demographic data, the laboratory parameters, the preoperative diagnosis, the surgery performed, the operation time, intra-or postoperative complications, the time to oral tolerance and the length of the hospital stay. RESULTS: The S group included 11 male and nine female patients with a mean age of 65 ± 12 (35-84) years, while the N group included 13 male and eight female patients with a mean age of 62 ±11 (46-79) years (p =0.448, p = 0.443, respectively). Anastomotic line bleeding was observed in eight (40%) patients in the S group and in one (4.7%) patient in the N group (p = 0.006). Dehiscence of the anastomosis line was observed in two (10%) patients in the S group and none in the N group (p =0.131). Anastomotic leakage developed in three (15%) patients in the S group and in one (4.7%) patient in the N group (p = 0.269). The mean hospital stay was 12.65 ± 6.1 days in theS group and 9.52 ± 2.9 days in the N group (p = 0.043). CONCLUSION: The 6-row 3-D linear cutter is a safe and easily applied instrument that can be used to create anastomoses in gastrointestinal surgery. The new stapler provides some usage benefits and is also superior to the standard linear cutter with regard to anastomotic line bleeding.